Associations Between Sleep Apnea and Subclinical Carotid Atherosclerosis: The Multi-Ethnic Study of Atherosclerosis. Issue 12 (December 2019) - Zhao, Ying Y.; Javaheri, Sogol; Wang, Rui; Guo, Na; Koo, Brian B.; Stein, James H.; Korcarz, Claudia E.; Redline, Susan
Abstract : Background and Purpose—: Many health effects of sleep apnea (SA) may be mediated through accelerated atherosclerosis. We examined the associations of snoring and several measurements of SA with subclinical carotid atherosclerosis in a large multiethnic population sample. Methods—: This analysis included 1615 participants (mean age, 68 years) from examination 5 (2010–2013) of the MESA study (Multi-Ethnic Study of Atherosclerosis). Sleep measures including SA (apnea-hypopnea index [4%], ≥15 events/hour) were derived from full in-home polysomnography. Carotid atherosclerosis was measured using high-resolution B-mode ultrasound. Multivariable linear and logistic regression models were used to evaluate the associations between sleep exposures with carotid intima-media thickness and the presence of carotid plaque, respectively. Effect modification by age, sex, and race/ethnicity was examined. Results—: In multivariable analysis, SA was associated with an increased odds of carotid plaque presence in individuals aged <68 years (odds ratio, 1.47; 95% CI, 1.05–2.06) but not in older individuals (odds ratio, 0.95; 95% CI, 0.67–1.37; P interaction=0.078). Greater hypoxemia (sleep time <90% saturation) was associated with increasing carotid intima-media thickness in younger (0.028±0.014 mm) but not in older individuals (−0.001±0.013 mm; P interaction=0.106). Self-reported snoring was not associated with carotid atherosclerosis. In assessing race-specific outcomes, greater hypoxemia was associated with increased carotid intima-media thickness in blacks (0.049±0.017 mm; P interaction=0.033). Conclusions—: In this large multiethnic population-based sample, sleep disturbances are associated with subclinical carotid atherosclerosis in both men and women, particularly in those <68 years of age. The mechanisms underlying the association between SA and carotid atherosclerosis may differ for carotid plaque and carotid intima-media thickness. Abstract : Supplemental Digital Content is available in the text.